How Cataract Extraction Helps in Improving Aqueous Outflow? - Farhan Ali, Hafiza Sadia Imtiaz, Irfan Qayyum Malik (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess changes in Anterior Chamber angle depth and width induced by phacoemulsification and intraocular lens implantation in normal population using anterior segment optical coherence tomography (AS-OCT). Study Design: Quasi experimental study. Study Place and Duration: Eye Department of DHQ-Teaching Hospital Gujranwala, from January, 2018 to June 2018. Material and Methods: All patients of both genders with senile cataract, having uneventful cataract surgery were randomly included in this study. After routine ophthalmic examination, pre-operative intraocular pressure (IOP) using Goldmann applanation tonometer along with anterior segment OCT for measuring angle parameters was done in the temporal quadrant of respected eye at the time of admission. Post-operatively the same procedure was repeated at the time of discharge. A P-value ? 0.05 was considered to be statistically significant. Results: Out of 82 patients, 44 (53.7%) were male and 38 (46.3%) were female. Mean Axial length recorded was 23 ± 1.2 mm with mean IOL power of 22.0 ± 3.2D. Mean Pre-op Trabecular Iris Angle (TIA) was 41.5 ± 8.7° that widened to 48.6 ± 8.3° post-operatively while Mean pre-op Angle opening distance (AOD-500 µm) recorded was 447.5 ± 149.8 µm that increased to 609.5 ± 169.8 µm post-operatively. Similarly, Mean pre-op IOP recorded was 16.8 ± 2.8 mm Hg that reduced to 15.1 ± 2.9 mm Hg post-operatively. P-value of all three parameters turned out significant (< 0.05). Conclusions: Cataract extraction and IOL implantation causes an increase in anterior chamber angle depth and width along with a reduction in intra-ocular pressure which is a direct evidence of improved aqueous outflow. Key Words: Anterior chamber, Trabecular Meshwork, Angle, OIptical coherence tomography.